2016
DOI: 10.1002/aenm.201601956
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Silver Cathode Surface Treated with Scandia‐Stabilized Zirconia Nanoparticles for Intermediate Temperature Solid Oxide Fuel Cells

Abstract: This work introduces a novel silver composite cathode with a surface coating of scandia‐stabilized zirconia (ScSZ) nanoparticles for application in intermediate temperature solid oxide fuel cells (IT‐SOFCs). The ScSZ coating is expected to maximize the triple boundary area of the Ag electrode, ScSZ electrolyte, and oxygen gas, where the oxygen reduction reaction occurs. The coating also protects the porous Ag against thermal agglomeration during fuel cell operation. The ScSZ nanoparticles are prepared by sputt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…To prevent particle agglomeration in a porous Ag layer, researchers considered the use of composite cathodes, in which Ag particles were coated with a layer of an oxygen-conducting electrolyte material. For this purpose, various technologies were applied such as aerosol-assisted chemical vapor deposition (AACVD) [ 67 ], atomic layer deposition (ALD) [ 68 ], sputtering [ 69 ], and infiltration [ 70 ].…”
Section: Electrodeposition Technology For the Fabrication Of Sofc Air Electrodes With Increased Performancementioning
confidence: 99%
“…To prevent particle agglomeration in a porous Ag layer, researchers considered the use of composite cathodes, in which Ag particles were coated with a layer of an oxygen-conducting electrolyte material. For this purpose, various technologies were applied such as aerosol-assisted chemical vapor deposition (AACVD) [ 67 ], atomic layer deposition (ALD) [ 68 ], sputtering [ 69 ], and infiltration [ 70 ].…”
Section: Electrodeposition Technology For the Fabrication Of Sofc Air Electrodes With Increased Performancementioning
confidence: 99%
“…(1) ALD oxide on metallic cathode ALD oxide overlayers (or overcoatings, capping layers), e.g., MnO x [31], ZrO 2 [28], SnO 2 [29], doped ZrO 2 [30,32], CeO x [33], on metal cathodes have been actively researched in recent years [28][29][30][31][32] because they can compensate for the low thermal stability of porous metal electrodes, and in some cases, can also improve the ORR activity. While oxide overlayers can be fabricated by using other techniques (sputtering [136][137][138], infiltration [139][140][141]), the conformal nature of the ALD process may further help to enhance the stability of metallic electrodes. The stabilization mechanism of metal nanoparticles by the oxide overlayer may include: (1) anchoring of metallic nanoparticles to the substrate, (2) stabilization of unstable metal surface atoms, which may impede the physical merging, and (3) Ostwald ripening of metallic nanoparticles [136,[142][143][144][145][146].…”
Section: Cathodementioning
confidence: 99%
“…In order to reduce the operation temperature down (e.g. 500ºC, Intermediate Temperature regime), use of catalysts is necessary [8]. The best catalyst for ORR is Pt or Ptalloys, which, however, is quite expensive.…”
Section: Introductionmentioning
confidence: 99%
“…The best catalyst for ORR is Pt or Ptalloys, which, however, is quite expensive. Recent experimental studies [8,9] suggested Ag as an alternative. Zhou and co-authors [10,11] in their theoretical calculations have shown that on the MnO2-terminated (001) LaMnO3 (LMO) surface Ag-doping significantly increases oxygen adsorption energy.…”
Section: Introductionmentioning
confidence: 99%